Gestão estratégica à luz das perspectivas do Balanced Scorecard: um estudo no Instituto Federal de Educação, Ciência e Tecnologia do Ceará - Canuto, Francisco Ebison Souto (2014)
The management of public and private institutions has, over the years, been making the work of managers increasingly challenging in these organizations. Many management systems have been or are still being created and used as a means to facilitate the management of existing institutions in Brazil and abroad, and, in many cases, not allowed to meet all the needs of these organizations, given the diversity of uncontrollable variables that exist, as well as the difficulty of making them measurable. Among the management tools created, the Balanced Scorecard (BSC) has been excelling, considering that the methodology is used to assist in the strategic management of these institutions. The governmental entity as a means to meet the needs of the population, has sought to utilize the BSC as a tool to maximize the achievement of institutional goals outlined with the society, thus improving its strategic management as well as fulfilling its institutional mission. To this end, the institutions of public higher education, in general, that have a poor strategic management culture, have the possibility of using the BSC to improve their performance. Thus, before the scenario presented and considering that in these institutions the use of this tool is not common rule, the present study aims to investigate how the current model of strategic management at the Instituto Federal de Educação, Ciência e Tecnologia do Ceará (IFCE) aligns itself to the perspectives of the Balanced Scorecard (BSC). To that end, the study adopts a mixed research approach, comprising the combination of qualitative elements, through an exploratory design, from a preliminarily review of bibliographic and documentary of the three main foundation themes of this work: Strategic Management, Higher Education Institutions and Balanced Scorecard (BSC). And quantitative elements, through a descriptive design, evidenced by the use of descriptive statistics and content analysis, from data collected from questionnaires and interviews with managers of strategic level existing in the institutions chosen for the study. Thus, this research can be regarded as a descriptive exploratory study, considering the need to explore and describe the behavior of this phenomenon from a single case study to be conducted at the IFCE. The survey results show that, considering the core activity of the institution, it prioritizes the perspective customers at the expense of other perspectives of the BSC, as well as the current model of strategic management of IFCE is partially aligned to that recommended by the BSC, considering the need to balance the form of implementation, monitoring and evaluation of their prospects. We can notice also that despite not being the BSC the current model used by IFCE to manage the institution, it is able to achieve its implementation.